Cel matrymonialny : rok z dziennika Tiffany Trott - Wolff, Isabel; Skarbinska, Alicja (Warszawa : Amber, 2001)
Polish translation of"Trials of Tiffany Trott". The story of a thirty-some year-old woman seeking a husband and love.
Translation of: Trials of Tiffany Trott.
Keywords: Single women -- England -- London -- Fiction; Dating (Social customs) -- England -- London -- Fiction